2014
DOI: 10.3329/bmrcb.v40i1.20333
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of oxidative stress by enalapril and valsartan in adrenaline treated rats: a comparative study

Abstract: Angiotensin (Ang II) II is known to promote oxidative stress in acute myocardial infarction (AMI). Inhibition of renin angiotensin system (RAS) or blockade of Ang II receptors may therefore be effective in reducing oxidative stress during AMI. The study evaluates and compares the protective effect of Angiotensin Converting Enzyme (ACE) inhibitor and AT 1 receptor blocker in adrenaline induced oxidative stress in rats. Rats were treated with two successive injections of adrenaline subcutaneously at a dose of 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
4
1
Order By: Relevance
“…It has been found that numerous drugs used to treat hypertrophic cardiomyopathy, such as ACE inhibitors, beta-blockers and calcium channel blockers, may have antioxidant effects [54][55][56]. Contrary to our expectations, we did not find statistically significant differences in any of the oxidative stress parameters between cats without treatment and those in the course of pharmacological therapy.…”
Section: Discussioncontrasting
confidence: 99%
“…It has been found that numerous drugs used to treat hypertrophic cardiomyopathy, such as ACE inhibitors, beta-blockers and calcium channel blockers, may have antioxidant effects [54][55][56]. Contrary to our expectations, we did not find statistically significant differences in any of the oxidative stress parameters between cats without treatment and those in the course of pharmacological therapy.…”
Section: Discussioncontrasting
confidence: 99%
“…This represents a pivotal role of adrenal central part in activating sympathetic system. 9 Although there is no known mechanism to relate central part of adrenal to hypoxia, some publications pointed that the central part of the adrenal is stimulated by hypoxia which subsequently increases the blood catecholamines. 22 A study performed on dogs by Favier et al showed that norepinephrine increased during hypoxia, but there was no increase in epinephrine levels, 23 which was different with our results for epinephrine.…”
Section: Discussionmentioning
confidence: 99%
“…8 Some researchers have suggested that angiotensin has a direct effect on vascular wall through an intracellular mechanism. 9 Unlike the known effects of angiotensin in atherosclerosis development, effects of catecholamines are different in ischemic and normal conditions. 10,11 Activity of vasoconstrictor system increases following hypoxia in order to increase the cardiac output and compensate the oxygen deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…[3536] They can reduce plasma malondialdehyde and increase erythrocyte glutathione content in rats. [37] The decreased lipid peroxidative stress by ACE inhibitors may result in the structural integrity of hepatocytes, thus improving the overall liver function.…”
Section: Discussionmentioning
confidence: 99%